Producer groups promote goat rearing in Uttarakhand - Maikhuri, Anil (Technical Centre for Agricultural and Rural Cooperation, 2018)
Smallholder farmers in northern India are turning to goat rearing to improve their incomes and food security. The Integrated Livelihood Support Project is providing training to these farmers on improved goat feeding and vaccination practices, increasing goat prices and contributing to the local economy.